If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12a + 7 = 7a + 2 Reorder the terms: 7 + 12a = 7a + 2 Reorder the terms: 7 + 12a = 2 + 7a Solving 7 + 12a = 2 + 7a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-7a' to each side of the equation. 7 + 12a + -7a = 2 + 7a + -7a Combine like terms: 12a + -7a = 5a 7 + 5a = 2 + 7a + -7a Combine like terms: 7a + -7a = 0 7 + 5a = 2 + 0 7 + 5a = 2 Add '-7' to each side of the equation. 7 + -7 + 5a = 2 + -7 Combine like terms: 7 + -7 = 0 0 + 5a = 2 + -7 5a = 2 + -7 Combine like terms: 2 + -7 = -5 5a = -5 Divide each side by '5'. a = -1 Simplifying a = -1
| 3(5x-3)-10=-34 | | 49=26-8(3-5w) | | 8.833x^2-1.422x+0.5842=0 | | (2a+7)(4a+10)= | | 10x-5-4x-3+2=0 | | -6=3(3x-5) | | 7x+4=45 | | -12=2(5x-1) | | 21x+15=15 | | -w-2=42 | | 0=x^2+6x-8 | | 6a+2=-a+30 | | (xy)(x^2y)(x^2y)(x^2y)(x^2y)=0 | | 1x+4y=168 | | 21x+5=15 | | x^2-4x-37=0 | | 3x^2+9x-2=-4 | | (xy)(x^2y)(xy)(x^2y)(xy)(x^2y)(xy)(x^2y)=0 | | 3x-5x=8-9 | | log*5(-6-2x)=2 | | (x^2D^2-4xD+6I)y=C | | (xy)(x^2y)(xy)(x^2y)(xy)(x^2y)=0 | | 15y+4=24 | | (5y+6)-(3y+4y)=10 | | a+4=-5a+5 | | 2.7x=0 | | -4b-5=10 | | z^3+3z^2+3z+1=0 | | -5(2y-6)-y=-3(y-3) | | n^2=3n+10 | | (x^9y)(x^9y)(x^9y)(x^9y)(x^9y)(x^9y)(x^9y)(x^9y)(x^9y)=0 | | 28x^8+16x^3-20x^6+12= |